PERANCANGAN SISTEM INFORMASI PENGELOLAAN PENGANGKUTAN SAMPAH BERBASIS WEBSITE - Maria Krisnawati; Rafi Aldiansyah (Jurnal Ilmiah Dinamika Teknik, 2020)
Abstract Management of the waste transportation system is one of the service systems provided by the government to the community in terms of environmental cleanliness. The waste management information system that is still manual makes it difficult for users in terms of monitoring and managing the garbage transportation system. The author designed a web-based waste management information system using the PHP, HTML and CSS languages. The system was built, besides being used as a data base storage and member registration, system operators can track the fleet with the help of the OpenStreetMap (OSM) application. The information system built also allows interaction with the community through online system registration. Making a system starts from identifying system requirements, such as creating context diagrams, data flow diagrams and entity relationship diagrams. Next is the design of data base and form which is then done by designing web applications. The results of making the web are several display menus that can be used by the public and managers Keywords: waste collection, information systems, GPS, OpenStreetMap